Coping with the challenges of mass migration : reception, distribution and integration of refugees in German Municipalities since 2015 - Hunger, Uwe (Array, 2019)
This article demonstrates how challenging the current migration is for the local level in Germany. As highlighted in the article, the integration of refugees mainly takes place at the local level, in the municipalities. The municipalities are responsible for a wide range of services, which include the implementation of the Residence Act, granting of social benefits, provision of health care services, accommodation, organization of integration and German language courses, provision of early childhood and school education, as well as support for labor market integration. The municipalities exercise considerable discretion as to how they operate these services and in effect, even though it is technically within the federal level’s jurisdiction, municipalities have some political influence regarding the right of residence. However, the degree of involvement among German municipalities varies and the role they play in integration often depends on the history of migration within their borders, past development of migrant communities, their own financial situation and infrastructure, as well as how the public engages with the issue. Thus, the political action (or non-action) of the municipalities will be decisive in the long-term integration process of refugees.